2022
DOI: 10.3389/fmicb.2022.838383
|View full text |Cite
|
Sign up to set email alerts
|

Wild Boars as an Indicator of Environmental Spread of ESβL-Producing Escherichia coli

Abstract: Antimicrobial resistance (AMR) represents an increasing issue worldwide, spreading not only in humans and farmed animals but also in wildlife. One of the most relevant problems is represented by Extended-Spectrum Beta-Lactamases (ESβLs) producing Escherichia coli because they are the cause of important infections in human. Wild boars (Sus scrofa) as a source of ESβLs attracted attention due to their increasing density and their habits that lead them to be at the human-livestock-wildlife interface. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…All of the wild boar amikacin-resistant E. coli harbored AMEs gene, particularly Aac(6′)-Ib . Additionally, Poirel et al [ 49 ] and Mercato et al [ 51 ] reported that the Aac(6′)-Ib gene was the most frequently found one in game animals.…”
Section: Discussionmentioning
confidence: 99%
“…All of the wild boar amikacin-resistant E. coli harbored AMEs gene, particularly Aac(6′)-Ib . Additionally, Poirel et al [ 49 ] and Mercato et al [ 51 ] reported that the Aac(6′)-Ib gene was the most frequently found one in game animals.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted in a similar manner [i.e. using cephalosporin-additive or the specific-selective agars) to investigate the prevalence of ESC resistance in E. coli isolated from terrestrial wild animals worldwide, including macaque (0%) and wild boars (33.0%) in Algeria [19]; wild boars (4.5%) in Spain [20]; various wild mammals (1.5%) in France [21]; wild boars (1.2%) and ruminants (1.1%) in Germany [22]; wild boars (23.3%) in Italy [23]; badger (8.9%) and fox (11.53%) in Ireland [24]; red foxes (10.5%) and martens (7.5%) in Poland [25]; wild boars (14%) in Tunisia [26]; and raccoons (56.9%) in the United States [9]]. These results implied that the prevalence of ESC-resistant E. coli isolates from wild animals is greatly different by animal species, which is closely related to their habitat and/or feeding habit and country, and Japanese raccoon dogs are comparable to other terrestrial wild animals in terms of ESC-resistant E. coli reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…using cephalosporin-additive or the specific-selective agars) to investigate the prevalence of ESC resistance in E. coli isolated from terrestrial wild animals worldwide, including macaque (0%) and wild boars (33.0%) in Algeria [19]; wild boars (4.5%) in Spain [20]; various wild mammals (1.5%) in France [21]; wild boars (1.2%) and ruminants (1.1%) in Germany [22]; wild boars (23.3%) in Italy [23]; badger (8.9%) and fox (11.53%) in Ireland [24]; red foxes (10.5%) and martens (7.5%) in Poland [25]; wild boars (14%) in Tunisia [26]; and raccoons (56.9%) in the United States [9]]. These results implied that the prevalence of ESC-resistant E.…”
Section: Discussionmentioning
confidence: 99%
“…Human greed and commercial activities guided by hunting culminated on wild boar release, intentional scape and spreading in all six Brazilian biomes, including national and state preservation units, agricultural lands, and livestock pastures, with similar wide spreading in the USA, invading 35/50 (70%) states [ 97 , 98 ]. Surprisingly, wild boars have been reportedly indicated as a One Health concern worldwide only (and recently) for circulating zoonotic protozoa and viruses in Portugal [ 99 ] and dissemination of antimicrobial resistant E. coli in Northern Italy, suggesting wild boar role as antibiotic resistance spreader, requesting inclusion in surveillance programs [ 100 ].…”
Section: The Wild Boar Problem Demands a One Health Approachmentioning
confidence: 99%